Microbially produced imidazole propionate impairs prostate cancer progression through PDZK1 - Shengkai Jin; Yuhua Zhou; Jing Lv; Yichen Lu; Yuwei Zhang; Menglu Li; Ninghan Feng (Molecular Medicine)
Abstract Background A close relationship exists between castration-resistant prostate cancer (CRPC) and histidine metabolism by gut microbes. However, the effects of the histidine metabolite imidazole propionate (IMP) on prostate cancer (PCa) and its underlying mechanisms are not well understood. Methods We first assessed the effects of IMP on cell proliferation and migration at the cellular level. Subsequently, we investigated the mechanism of action of IMP using transcriptome sequencing, qPCR, and Western blot analysis. Finally, we validated our findings in vivo using a mouse model. Results Histidine had no effect on PCa cell proliferation; however, IMP significantly inhibited the proliferation and migration of PC3 and DU145 cells. Mechanistic studies indicate that IMP exerts its effects by upregulating PDZK1 expression, which subsequently inhibits the phosphorylation of the PI3K-AKT pathway. Conclusions In conclusion, IMP significantly inhibits the progression of PCa, offering new insights into potential treatments for CRPC.